2020
DOI: 10.20944/preprints202004.0126.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cold Atmospheric Plasma for COVID-19

Abstract: The recent pandemic has greatly stressed supply chains, treatment modalities, and medical resources. Cold atmospheric plasma (CAP) has been used for a wide range of applications in biomedical engineering due to its many components including electrons, charged particles, reactive oxygen species (ROS), reactive nitrogen species (RNS), free radicals, ultraviolet (UV) photons, molecules, electromagnetic fields, physical forces, and electric fields. In this manuscript, we develop CAP devices for COVID-19. Our manus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This was achieved mainly through hydroxyl radicals and reactive species it generated through interacting with other species via activating ERα/STAT3 and EGFR/STAT3 signaling. We recommend exposing mucosal cells to CAP for 30s or 30% PAM for 1 min as a preventative that could reduce SARS-CoV-2 infection for 5-12 h. Specifically, nose/mouth spray and other products in the form of aerosols may be effective in a therapeutic setting, and handwash made of PAM may also help prevent SARS-CoV-2 infection in a sense that PAM could disable virus binding by damaging the RBD spike 110 in addition to the reported efficacy on mucosal host cells here 111 . The epidemiologic observation that females are less likely to develop severe COVID-19 could partially be explained by the finding that the female sex hormone E2 resembles CAP in triggering ACE2 nuclear translocation and, importantly, is supportive to the protective role of ACE2 internalization in fighting against severe SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved mainly through hydroxyl radicals and reactive species it generated through interacting with other species via activating ERα/STAT3 and EGFR/STAT3 signaling. We recommend exposing mucosal cells to CAP for 30s or 30% PAM for 1 min as a preventative that could reduce SARS-CoV-2 infection for 5-12 h. Specifically, nose/mouth spray and other products in the form of aerosols may be effective in a therapeutic setting, and handwash made of PAM may also help prevent SARS-CoV-2 infection in a sense that PAM could disable virus binding by damaging the RBD spike 110 in addition to the reported efficacy on mucosal host cells here 111 . The epidemiologic observation that females are less likely to develop severe COVID-19 could partially be explained by the finding that the female sex hormone E2 resembles CAP in triggering ACE2 nuclear translocation and, importantly, is supportive to the protective role of ACE2 internalization in fighting against severe SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…1 A), which exhibit favorable behavior for biomedical applications. 57 The biophysical details are discussed in our previous paper 8 …”
Section: Figurementioning
confidence: 99%
“…[5][6][7] The biophysical details are discussed in our previous paper. 8 We employed argon(Ar)-fed CAP treatments to inactivate SARS-CoV-2 on various surfaces including plastic, metal, cardboard, basketball composite leather, football leather, and baseball leather. The CAP device consists of a two-electrode assembly with a powered needle electrode and a grounded outer ring electrode, which were connected to a high voltage transformer.…”
mentioning
confidence: 99%
“…Nelson and Berger (1989) demonstrated that O 2 plasma would be a very powerful biocidal agent against bacteria. Nowadays, NTP is utilized extensively in biomedical applications, including sterilization, disinfection, microbial, and biofilm inactivation, many of actual reviews are available, for example, Julák, Scholtz, and Vaňková (2018), Laroussi (2018) In connection with the Covid-19 pandemic, three following articles (Chen & Wirz, 2020;Cheng, Wong, Kwan, Hui, & Yuen, 2020;Verma, 2020) presenting the possible application of NTP against SARS-CoV-2 although only on a theoretical level have been published.…”
Section: Antiviral Mechanism Of Cold Atmospheric Pressure Plasmamentioning
confidence: 99%